Аналіз акустичної емісії в процесах механічної обробки з використанням вейвлет-пакетів - Шевченко, Вадим Володимирович; Заєць, Сергій Сергійович; Олінійчук, Антон Ігорович (НТУ "ХПІ", 2017)
В даній роботі були проведені дослідження акустичної емісії (АЕ) в рамках моніторингу процесів механічної обробки. АЕ безпосередньо пов’язана зі станом інструменту, так як акустична хвиля генерується за рахунок пластичної деформації, стирання, руйнування та поширення тріщин. У дослідженні, опублікованому в даній роботі було виміряно декілька параметрів АЕ під час механообробки. В той час як ці параметри вказують на ступінь зносуріжучого інструменту, їх інформативність для промислового використання обмежена. Для набуття більшої інформативності була використана теорема вейвлет-пакетів (ВП), за допомогою якої ми ввели додаткові коефіцієнти ентропію та силу. Отримали адекватну модель для визначення стану інструменту.

The problem of safe operation and efficient operation of complex technical systems and equipment hazardous industries. A significant depreciation of industrial equipment involves the search for new approaches to solving the problems that stand before the technical diagnosis. The aim was to develop a system of analysis of acoustic emission (AE) for machining processes. Originally performed by analysis of informative parameters of AE. After the experiment, it was found that their information content is insufficient for industrial use. To solve this problem, we used wavelet packet method. Using advanced options and forces of entropy, solved the problem, which was confirmed experimentally. Parameter energy in conjunction with the parameters of AE is a measure of tool wear. When we register peak signals a change in the behavior of other parameters, leading to the rejection of the system. Informative parameters AE can establish dependency on energy consumption equipment that gives a fairly accurate results. The downside can be assumed that all of these parameters and their combination is sensitive to the conditions and needs careful care facilities.
Analysis of acoustic emission in the processes of machining using wavelet packets
Keywords: метод акустичної емісії; руйнування; механічна обробка; аналіз АЕ; acoustic emission; wavelet packet; entropy; machining; analysis of AE